Residual analysis of chitosan-based agronanofungicides as a sustainable alternative in oil palm disease management - Maluin, Farhatun Najat; Hussein, Mohd Zobir; Yusof, Nor Azah; Fakurazi, Sharida; Maznah, Zainol; Idris, Abu Seman; Hilmi, Nur Hailini Zainol; Daim, Leona Daniela Jeffery (Nature Research, 2020)
The nanoformulations of pesticides have shown great interest from many parties due to their slow release capability and site-specific delivery. Hence, in this work, a new nanoformulation of a fungicide, namely chitosan-hexaconazole nanoparticles with a mean diameter size of 18 nm was subjected to the residual analysis on oil palm tissue, leaf and palm oil (crude palm oil and crude palm kernel oil) using a quick, easy, cheap, effective, rugged and safe (QuEChERS) method coupled with the gas chromatography–micro electron capture detector (GC–µECD). The chitosan-hexaconazole nanoparticles were applied using the trunk injection method at 4.5 g a.i./palm (standard single dose) and 9.0 g a.i./palm (double dose). The fungicide residue was analyzed at 0 (6 h after application), 1, 3, 7, 14, 30, 60, 90, and 120 days after treatment. The palm oil matrices; the crude palm oil (CPO) and crude palm kernel oil (CPKO) were found to be residue-free. However, it was observed that high accumulation of the fungicide in the stem tissue and leaf after the treatment using the chitosan-hexaconazole nanoparticles, which is good for better bioavailability for the treatment of the fungi, Ganoderma boninense. The dissipation kinetic at double dose treatment in the tissue and leaf was found to govern by the second-order kinetic with half-lives (t1/2) of 383 and 515 days, respectively.